Non-equivalence at word level in the English translation of Fuadi’s Rantau 1 Muara - Iwik Pratiwi (UPT P2M Politeknik Negeri Malang, 2013)
Rantau 1 Muara is the last novel of the trilogy is the last trilogy of Negeri 5 Menara, written by Anwar Fuadi. The novel settings include, one of them, the unique life of pesantren. Because it is so unique, the translation into English may face problems as many of the concepts talked about are bound to Javanese or Islamic culture. Thus, it can be predicted that some problems should appear. To prove this, the writer translates one chapter and report the problem and how to solve the problems. This